Faktor Penyebab Banyak Anak Pada Pus Nelayan Di Desa Subang Jaya Lampung Tengah - Muhamad Salahudin Alayubi; I Gede Sugiyanta; Nani Suwarni (JPG (Jurnal Penelitian Geografi), 2019)
This study aimed to examine factors that caused the number of children by reproductive agecouple (PUS) of fishermen family in Subang Jaya Village,Central Lampung District.The method used descriptive method.The research population was 110 PUS. Collecting data was did by observation technique, questionnaires ,and,documentation.Analysis of databy tabulation technique and percentage. The results of this study show:(1)As much as 77.27% of PUS got married at young age (21 years) and tend to have many children.(2)The longer of the marriage period (10-19) years,as much as 66% tend to have many children.(3)As much as 81.8% of respondents participated in family planning program but followed it on average after having more than 2 children. (4)59.09% of respondents want to have an average of 4 children. (5)As much as 100% of PUS agreed that marriage must have children,child wasgiftfrom God,child as marriage bond,they are the inheritance of parent's estate and the value of the child in the family is still very strong in the PUSof fishermen family.Penelitian ini bertujuan untuk mengkaji faktor yang menyebabkan banyaknya jumlah anak PUS keluarga nelayan di Desa Subang Jaya Kabupaten Lampung Tengah. Metode yang digunakan metode deskriptif. Populasi penelitian sebanyak 110PUS.Pengumpulan data dengan teknik observasi, kuesioner, dan dokumentasi. Analisis data dengan teknik tabulasi dan presentase.Hasil penelitian ini menunjukan:(1)sebanyak77,27% PUS melakukan perkawinan muda (21tahun) cenderung memiliki anak banyak. (2) Semakin lama masa perkawinan (10-19) tahun sebanyak 66% cenderung memiliki anak banyak.(3)Sebanyak 81,8% responden mengikuti program KB namun mengikuti program KB nya rata-rata setelah memiliki anak lebih dari 2.(4)Sebanyak 59,09% rata responden ingin memiliki rata-rata 4 anak.(5)Sebanyak 100% PUS setuju perkawinan harus memiliki anak,anak karunia Tuhan,anak ikatan perkawinan,pewaris harta orang tua dan terbuktilah nilai anak dalam keluarga masih sangat kuat pada PUS keluarga nelayan.Kata kunci: jumlah anak, keluarga nelayan, penyebab